(untitled) (Annals of Medical Research, 2021)
Aim: Cerebral palsy (CP) is the most common neuromuscular disorder of the childhood for which various therapeutic modalities available, which range from conservative approach to surgery. In the present study, we aimed to evaluate the efficacy of robot assisted gait training in patients with cerebral palsy following botulinum toxin injections in the lower extremity.Material and Methods: The study enrolled children (4 to 16 years of age) diagnosed with CP presenting to the Physical Therapy outpatient clinic who had level 1 to 4 walking difficulty associated with lower extremity spasticity according to the GMFCS (Gross Motor Function Classification System) and received botulinum toxin injections to the lower extremity within the previous month. CP patients received robot-assisted gait training five times a week over 3 weeks for a total of 15 sessions by two physiotherapists under the supervision of a physician. Study assessments included measurements of the range of motion (ROM) of the joints and the popliteal angle, GMFCS-88, Berg Balance Scale (BBS) and the and Pediatric Functional Independence Measure (WeeFIM) which were conducted before and after treatment.Results: A total of 14 pediatric patients (8 girls, 6 boys) were included in the study. The mean age of the children was 9.93±3.54 years. A statistically significant reduction in the popliteal angle was found at post-treatment assessments compared to baseline. Berg Balance Scale, WeeFIM and GMFCS-88scores were significantly improved following treatment.Conclusion: Robot-assisted gait training following botulinum toxin injections were found to provide marked improvements in motor functions, balance, spasticity and functional status in children with CP.